A bibliometric analysis of the top 100 most cited articles on corticospinal tract regeneration from 2004 to 2024 - Saijilafu,; Ye, Ling-Chen; Li, Huanyi; Li, Haokun; Lin, Xinyi; Hu, Kehui; Huang, Zekai; Chimedtseren, Chimedragchaa; Fang, Linjun; Saijilahu,; Xu, Ren-Jie (Frontiers in Neuroscience, 2025)
ObjectiveHere, bibliometric and visual analytical techniques were employed to assess the key features of the 100 most cited publications concerning corticospinal tract (CST) regeneration.MethodsResearch was conducted within the Web of Science Core Collection to pinpoint the 100 most cited publications on CST regeneration. From these, comprehensive data encompassing titles, authorship, key terms, publication venues, release timelines, geographic origins, and institutional affiliations were extracted, followed by an in-depth bibliometric examination.ResultsThe 100 most cited publications were all published between 2004 and 2024. These seminal papers amassed an aggregate of 18,321 citations, with individual citation counts ranging from 83 to 871 and a median of 136 citations per paper. Schwab M. E., stood out as the most prominent contributor, with significant authorship in 9 of the 100 papers. The United States dominated the geographical distribution, accounting for 49 of the articles. With 17 publications, the University of California System led the institutional rankings. A thorough keyword analysis revealed pivotal themes in the field, encompassing the optic nerve, gene expression, CST integrity and regeneration, diffusion tensor imaging, myelin-associated glycoproteins, inhibitors of neurite outgrowth, and methods of electrical and intracortical microstimulation.ConclusionThis investigation provides a bibliometric analysis of CST regeneration, underscoring the significant contribution of the United States to this field. Our findings unveiled the dynamics and trends within the field of CST regeneration, providing a scientific foundation for advancing clinical applications. Building on this analysis, the clinical application of CST regeneration should be optimized through interdisciplinary collaboration, enabling the exploration and validation of a variety of therapeutic approaches, including the use of neurotrophic factors, stem cell therapies, biomaterials, and electrical stimulation. Concurrently, additional clinical trials are necessary to test the safety and efficacy of these therapeutic methods and develop assessment tools for monitoring the recovery of patients. Furthermore, rehabilitation strategies should be refined, and professional education and training should be provided to enhance the understanding of CST regeneration treatments among both medical professionals and patients. The implementation of these strategies promises to enhance therapeutic outcomes and the quality of life of patients with spinal cord injury (SCI).